ПРОБЛЕМА АГРЕСИВНОЇ ПОВЕДІНКИ ПІДЛІТКІВ ЯК СКЛАДОВА ДЕВІАНТНОСТІ (Педагогіка вищої та середньої школи, 2007)
In given clause is considered as aggressive, aggression become in the future the basic reason for display deviation of behaviour of the teenagers; as the cruelty and aggressive behaviour are caused with disputed situations in school collective.